Les Tendances Actuelles De La Mondialisation De La Science Mondiale - Volume 2 2020
DOI: 10.36074/03.04.2020.v2.09
|View full text |Cite
|
Sign up to set email alerts
|

Бронхіальна Астма Як Атопічне Захворювання

Abstract: Positive influence on the psychological state of pregnant women is the presence of her husband during childbirth, moderate physical activity, outdoor walking, attending courses by young parents during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…For groups B2 and A, the availability of births in history did not have a significant difference. In group without psychological disorders 114 women (91.9%) gave births with the presence of a partner, in 87.5% husbands were partners, that fact positively affects the psychological health of women and helps to overcome stress caused by childbirth [6,8], in other cases, 4,4% friends and mothers were partners. For women with subclinical manifestations, partner births were 75.9% (63 women), and in the group with pronounced signs PPD -66.6% (20 women).…”
Section: Pict 1 Depth Of Postnatal Depressive Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…For groups B2 and A, the availability of births in history did not have a significant difference. In group without psychological disorders 114 women (91.9%) gave births with the presence of a partner, in 87.5% husbands were partners, that fact positively affects the psychological health of women and helps to overcome stress caused by childbirth [6,8], in other cases, 4,4% friends and mothers were partners. For women with subclinical manifestations, partner births were 75.9% (63 women), and in the group with pronounced signs PPD -66.6% (20 women).…”
Section: Pict 1 Depth Of Postnatal Depressive Disordersmentioning
confidence: 99%
“…Currently, studies are conducted to find out the correlations between deviations of hormonal parameters before and during pregnancy with the risk of depression after delivery. Of great importance is the change in the system of "hypothalamus-pituitary-adrenal gland" and the thyroid gland [7,8]. It is believed that vitamin D deficiency in 2-3 trimester can be a factor in the development of PPD [2,7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…
Among all patients with allergic diseases, 300 million people suffers from bronchial asthma. The pathoimmune mechanisms of asthma has to be studied, particularly at the gene-molecular level [1].A large epidemiological study -The World Health Organisation, conducted on behalf of the WHO in 70 countries (out of 192), showed that the prevalence of diagnosed asthma in adults is 4.3%, ranging from 0.2% in China to 21% in Australia. Atopic pathology has acquired the status of a significant socioeconomic, medical problem for mankind.
…”
mentioning
confidence: 99%
“…Among all patients with allergic diseases, 300 million people suffers from bronchial asthma. The pathoimmune mechanisms of asthma has to be studied, particularly at the gene-molecular level [1].…”
mentioning
confidence: 99%